A systematic review and meta‐analysis of acute severe complications of pediatric anesthesia. Issue 11 (21st September 2015) - Mir ghassemi, Asadollah; Neira, Victor; Ufholz, Lee‐Anne; Barrowman, Nick; Mulla, Jamila; Bradbury, Carol L.; Bould, Matthew Dylan; Thomas, Mark
Summary Background Quantification of acute severe complications of pediatric anesthesia is essential to plan clinical guidelines and educational curricula. Aim Our aim was to identify complications in terms of frequency and outcomes. Methods We defined acute severe complications as an unexpected perioperative event, which without intervention by the anesthesiologist within 30 min may lead to disability or death. A systematic search was performed using MEDLINE, EMBASE, and CINAHL. Screening and data extraction were performed independently. Assessment of bias was conducted using GRADE guidelines. Results Of 3002 abstracts, 25 met all inclusion criteria. The most common acute severe complications in pediatric anesthesia are related to airway management and respiratory system, followed by cardiovascular events. There was a great variation in reporting the methods, particularly poor definitions of diagnostic criteria for complications. Data were heterogeneous and pooled estimates may not be generalizable. Some studies failed to define potential source of bias, explain how missing data were addressed, describe acute severe complications, and had incomplete postoperative follow‐up. Conclusion The data on pediatric anesthesia acute severe complications are poorly defined with large variation in the specificity of diagnostic reporting even within studies. We suggest that it is vital for future studies in this area to be based on a standardized system of diagnostic reporting (possibly with a hierarchical system of coding) with adequate description of population details to describe heterogeneity of data.